2023
DOI: 10.1097/mbp.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to medication adherence in patients with hypertension in Iran: a systematic review study

Golara Maleki,
Rohollah Norian,
Babak Moeini
et al.

Abstract: Objectives This study aimed to review the available studies of the factors in Iranian hypertensive patients’ adherence to drug treatment. Methods Four Persian databases and seven English databases were searched. The articles, which were published from 2000 to 2022 in Persian and English and examined the adherence to drug treatment in the Iranian population of adults with high blood pressure, were reviewed. Based on the primary examination, 31 of the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(181 reference statements)
1
0
0
Order By: Relevance
“…The results of this study demonstrated that adherence to medication had a significant relationship with illness perception and all HL dimensions. This result is in line with previous studies which reported the strong association between medication adherence and health literacy among older adults hypertensive patients ( 36 ) and people with hypertension ( 25 , 37 ). Baharvand et al ( 38 ) found that perceptions of illness consequences could significantly predict treatment adherence.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study demonstrated that adherence to medication had a significant relationship with illness perception and all HL dimensions. This result is in line with previous studies which reported the strong association between medication adherence and health literacy among older adults hypertensive patients ( 36 ) and people with hypertension ( 25 , 37 ). Baharvand et al ( 38 ) found that perceptions of illness consequences could significantly predict treatment adherence.…”
Section: Discussionsupporting
confidence: 93%